Homofobia familiar: abrindo o armário entre quatro paredes - Toledo, Lívia Gonsalves (2013)
Sexuality device authorizes families to become the guardians of its members’ sexuality, ensuring the exclusion of any kind of dissidence from heteronormativity by means of reinforcement of homophobia. This paper presents the analyses of female participants who are dissident of heteronormativity. They were accessed through snow-ball technique and were interviewed. After transcribing their interviews, the researcher produced narratives of their lives with were corroborated with the participants. Data were analyzed from a poststructuralist perspective. By then, we privileged the study of the manifestation of homophobia in the family, developing a genealogy of their detractors effects, but also highlighting modes of resistance to it. This locus of manifestation of homophobia, obscured by the intimacy of the private world, is still a fairly discussed topic in national studies and maximizes the damage caused by discrimination in macro social spaces. We pointed out, then, family as an important target of action for public policies which aim the protection of human and civil rights, as well as all kinds of violence and discrimination.